Metrology, standardization and conformity assesment - Burova, М. Y.; Varavina, О. P.; Yatskevich, О. О. (My University, 2023)
The manual contains a course on discipline "Metrology, standardization and conformity assesment". The manual provides a holistic, systematic understanding of the current state of the standardization system, metrological activities, technical regulation and conformity confirmation procedure, the activities of international and regional standardization and certification systems around the world. Intended for students of the 5th course of specialty 185 "Oil and gas engineering and technology".
Метрологія, стандартизація та підтвердження відповідності
Keywords: compendium of lectures; state metrological system; International metrological organizations; classification of measurements; concept of standardization; regulatory documents